Seedling growth and physiological responses of Perth’s eucalypts to soil-induced stresses - Farifr, Eiman (Curtin University, 2010)
Perth’s Swan Coastal Sand Plain soils are typically nutrient impoverished, and the native trees of the region are therefore adapted to maximise nutrient uptake. Although the dune systems here are generally not known to be particularly saline or alkaline, there are areas that susceptible to salinity, flooded and elevated pH, especially those that have been modified by human activities. This study investigated the seedlings growth of three Eucalyptus species (Corymbia calophylla, Eucalyptus gomphocephala and E. marginata) to three environmental stress; salinity waterlogging and alkalinity in a greenhouse at Curtin University to assess their relative tolerance to these stressors, and hence understand more about their potential use in landscape restoration and rehabilitation. Knowing the seedling growth and physiological responses of three prominent Perth eucalypts to soil-induced stresses provides us with invaluable knowledge for rehabilitating and restoring Perth’s urban bushland.For the salt tolerance experiment, seedlings of the three species were subjected to 81 days growing in potting mix watered weekly with either 0, 50, 100, 150, 250 mM NaCl solutions. Measurements of relative plant growth, biomass allocation and leaf water loss and seedling survival suggested that E. gomphocephala was the most tolerant. Survival data suggests that E. gomphocephala seedlings have shown ability to cope with a weekly dosage of NaCl solution much greater than 0.25 M, and at least survived for more than 11 weeks under moderately saline conditions. Corymbia calophylla, and E. marginata were the least tolerance with more than half the seedlings succumbing to salt solutions > 250 mM NaCl.A flooding experiment, caused by prolonged inundation of water, lasting for 70 days, all three species grew most vigorously in well watered condition but when waterlogged condition E. gomphocephala and E. marginata seedlings grew slowly and became more water stressed compared to C. calophylla seedlings. These finding suggest that although E. gomphocephala and E. marginata can occurs in wetter areas of Perth’s Swan Coastal Plain they are not flood tolerant. C. calophylla is a common tree species in the moderately wet lower south-west of Western Australia; it is less common north of Perth where it is restricted to river valleys (Powell 2009). This may explain Marri’s ability to physiologically tolerate seasonal flooding (i.e. no significant reduction in stomatal conductance or transpiration rate), despite a reduction in seedling growth.A liming experiment, was conducted with 20% w/w crushed and sifted Tomala limestone add to potting mix to increase soil pH. The pot trial was conducted over 82 days. E. gomphocephala is restricted soils overlying limestone on Perth’s Swan Coastal Plain, and according to total seedling dry weight data and calculated relative growth rates coped best in a limestone-enriched soil. However, when examining all the growth and physiological data collected C. calophylla appears to be the most tolerant, with no significant difference in leaf allocation or leaf water loss between the well-watered controls and the limestone-enriched treatments. E. marginata was the least tolerant with a 14% reduction in stomatal conductance.As seedlings, E. marginata was the least tolerant to the three soil-induced stresses (i.e. flooding, salinity, alkalinity) imposed. The next most tolerant species, E. gomphocephala wasn’t the most tolerant to an increase is soil alkalinity, although it displayed the least change in seedling dry weight and relative growth rate. C. calophylla was the most tolerant of the three eucalypts to the three stressors. However soil-induced stresses will last for longer than the 70-80 days when plants are growing in more natural environments than the seedlings were exposed to in these experiments. By itself, these results will assist Perth’s urban land managers in understanding how these tree species respond at the seedling stage to three important soil-induced stressors, more work is required to understand how the observed responses after seedling physiology and how long the seedlings can tolerate these extreme changes in their growing environment.